1988
DOI: 10.1002/ar.1092220112
|View full text |Cite
|
Sign up to set email alerts
|

Embryological development and prevalence of thumb flexion creases

Abstract: A study of the embryological development and morphology of the thumb flexion creases is presented. We used 178 human fetuses, at 6-20 weeks of gestational age, and 225 normal adults, aged 19-81 years, to observe the morphology and the timing and location of the appearance of the flexion creases. Most creases, that is, the regular, extra, and oblique creases, were found to develop concurrently with the appearance of the fetal volar pads, apparently independently of the thumb flexion movements. Although the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…However, repeated electromyogram in proband 5 with pes cavus from early childhood showed no abnormalities. The faint extension creases and mild contractures of the fingers are both likely to be caused by the aberrant fetal development, primarily caused by the AUTS2 defect or secondary through lack of movement in utero caused by the AUTS2 defect 24. As AUTS2 is highly expressed in the developing brain and the functional clues at the molecular and protein level so far also indicate an important role in neuron development, one could hypothesise that diminished movements in utero (for neurological reasons) are causing these defects 1 3 4 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, repeated electromyogram in proband 5 with pes cavus from early childhood showed no abnormalities. The faint extension creases and mild contractures of the fingers are both likely to be caused by the aberrant fetal development, primarily caused by the AUTS2 defect or secondary through lack of movement in utero caused by the AUTS2 defect 24. As AUTS2 is highly expressed in the developing brain and the functional clues at the molecular and protein level so far also indicate an important role in neuron development, one could hypothesise that diminished movements in utero (for neurological reasons) are causing these defects 1 3 4 5.…”
Section: Discussionmentioning
confidence: 99%
“…The elevations of the digital surfaces stained dark blue and grooves (creases) pale blue. Estimation of fetal age was based on the report by Kimura and Schaumann (1988). Staining with toluidine blue solution was useful in general, but it proved to be indispensable in embryos and early fetuses of less than about 10 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Published reports on digital flexion creases include studies of embryonic development (Popich and Smith, 1970;Kimura and Kitagawa, 1986;Kimura and Schaumann, 1988;Stevens et al, 1988) and variations in morphology of digital (Aue-Hauser, 1979, 1980Aue-Hauser et al, 1978, 1980Komatz et al, 19781, thumb (Kimura and Schaumann, 19881, and metacarpophalangeal (Okajima, 1966(Okajima, , 1968) flexion creases in healthy individuals and reports of unusual digital flexion creases in various medical disorders (e.g., DeJong and Platou, 1967;Hodes et al, 1978;Kida et al, 1974;Penrose, 1931;Rodewald and Wischerath, 1979;Zizmor, 1973). Recently, Kimura and Schaumann (1988) described two types of previously unrecognized flexion creases, i.e., the "oblique" crease and the "extra" crease on the thumb and found their frequencies to be similar in fetuses and in healthy, phenotypically normal adults. These authors suggested that, owing to their high frequency, the oblique and extra creases should be considered "regular" creases.…”
mentioning
confidence: 99%
“…The distal crease of the proximal interphalangeal crease and the accessory crease seem to develop in association with spontaneous flexion movement of the hand. These two creases are also permanent and do not change in number or appearance during the lifetime, unlike some secondary creases whose numbers tend to increase with age (Kimura & Kitagawa, 1986; Kimura & Schaumann, 1988; Kimura et al. , 1990).…”
Section: Relationship Between the Pads And Flexion Creases During Devmentioning
confidence: 99%
“…On the fingers/toes, the creases include the metacarpophalangeal/metatarsophalangeal crease, which separates the palmar/plantar and digital volar areas of the hand/foot, and the proximal and distal interphalangeal creases, associated with the interphalangeal joints. Unlike the other digits, the thumb typically has only one interphalangeal crease (Kimura & Schaumann, 1988). Although the proximal interphalangeal crease is generally considered to be a single crease, it is actually a configuration consisting of two distinct creases, the proximal and the distal.…”
Section: Nomenclature and Classification Of Pads And Flexion Creasesmentioning
confidence: 99%